From Pork to Performance - Custer, Samantha (World Bank, Washington, DC and AidData, 2016)
From pork to performance illuminates the politics of how public resources are spent and the difficulty of the ‘last mile’ of service delivery. Crumbling facilities, absentee teachers, and roads to nowhere waste resources and retard development in many countries around the world. These failures in last mile service delivery underscore a more intractable development problem, a breakdown in accountability relationships, as politicians and civil servants act with impunity to extract private benefits at the expense of public goods. This study examines the extent to which technology and transparency can disrupt this low accountability status quo through turning information into collective action to improve government performance by strengthening the accountability relationships between politicians, service providers and citizens. In 2010, a new president came to power in the Philippines with a compelling message, ‘no corruption, no poverty’, and embraced open government as a vehicle to burn avenues of retreat and advance governance reforms. This study features examples from five sectors, education, reconstruction, roads, municipal development, and tax collection – where government champions sought to open up the black box of service delivery and use digital platforms to disclose data and strengthen accountability. This research provides guidance for public, private, and civil society leaders committed to using technology and transparency to curb pork-barrel politics and create digital dividends for their communities. The study combines rigorous political economy analysis with practical diagnostic tools and recommendations for open government initiatives to go deeper in the Philippines and around the world.